(7/4)+1/5(x)-(3/2)=(4/5)x

Simple and best practice solution for (7/4)+1/5(x)-(3/2)=(4/5)x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7/4)+1/5(x)-(3/2)=(4/5)x equation:


x in (-oo:+oo)

(1/5)*x+7/4-(3/2) = (4/5)*x // - (4/5)*x

(1/5)*x-((4/5)*x)+7/4-(3/2) = 0

(1/5)*x+(-4/5)*x+7/4-3/2 = 0

1/4-3/5*x = 0 // - 1/4

-3/5*x = -1/4 // : -3/5

x = -1/4/(-3/5)

x = 5/12

x = 5/12

See similar equations:

| 3u=19.2 | | 16+8x=25+15x+3 | | 2-x=-30/(x-1) | | 48-3x=0 | | -12=-7k-5k | | 2-x=30/(x-1) | | 15t^2-22tv-5v^2=0 | | 2x/5+8=13/5 | | x-(10/(x-1))=4 | | -3x^2+4=4x | | -7n-n=-24 | | x+x=30-10 | | 5+3q-4=2q+1 | | x-10/(x-1)=0 | | (t-7)(t-7)=(t+7)(t+7)+168 | | x-(10/(x-1))=0 | | 4+6(6x-1)=-5(-x+5)-8 | | 9x-12-2x=11x+6 | | 11-9x-7-6x=7 | | (x-2)+2(x-2)-24=0 | | -2p-6p=-24 | | 7=8x-4 | | (4x^2+16x+16)(x-2)=x^2-4 | | 2x^4-7x^2+2=0 | | 2t-3=3(t-4) | | 2-0.6k=2 | | 36=3(4-x) | | 5x+x=8x+55+9x | | 25x-3=35x+5 | | 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 |

Equations solver categories